Preparedness for climate change in rural areas—case study in three southern Finnish villages - Ruponen, Josefiina; Tuominen, Kaisa; Vanhamäki, Susanna; Aarrevaara, Eeva (Frontiers in Climate, 2025)
The anticipated climate change is intensifying short-term extreme weather events and changing their timing and frequency. It is having harmful impacts on local living conditions, such as human safety and health. Different settlements will face different risks. This case study examines how rural residents are prepared for the short-term climate risks caused by extreme weather events in Southern Finland. It also explores how these skills can be improved through public participation, including raising awareness and knowledge sharing. The scope of the study covered rural residential areas, excluding agricultural land. The case study in three rural villages included knowledge sharing and workshops with residents, climate risk reviews based on literature and field observations, and small-scale surveys based on self-assessment on how the experienced preparedness had changed. The results demonstrate that residents in the target villages experience themselves to be relatively well prepared for climate risks. Nevertheless, awareness raising resulting in increased knowledge seemed to make a positive impact on the residents’ preparedness skills in the studied areas. On average 25% of the respondents experienced that their preparedness skills had increased during the process, although this number has to be treated with caution due to small sample size and the study setting. The results encourage similar studies on a larger scale in Finnish rural areas.